RANCANG WEB BASED SYSTEM UNTUK REKOMENDASI BUKU PERPUSTAKAAN MENGGUNAKAN COLLABORATIVE FILTERING (STUDI KASUS : PERPUSTAKAAN DAERAH KABUPATEN SUMBA BARAT) - Melinia Pedi Moli; Antar Maramba Jawa; Lidia Lali Momo (Indonesian Journal of Engineering and Computer Science (IJEC), 2025)
Modern life is a life marked by various advances in science, technology and cultural development. The characteristics of modern human life include being seen or measured by the level of ability and way of thinking, procedures and efforts with the characteristics of a rational life using logic, ratios, systems of order, calculations or calculations and methods, and information systems. One example is the regional library of West Sumba district. Until now, library management is still largely done manually, starting from recording collections, arranging bookshelves, so that the process of borrowing and returning books. With this library information system, it can ease the work of library staff in managing member data, book data, transaction data and making reports that previously still used manual recording, so that the recording is more accurate.